2020
DOI: 10.1177/0014402919893695
|View full text |Cite
|
Sign up to set email alerts
|

District-Level Achievement Gaps Explain Black and Hispanic Overrepresentation in Special Education

Abstract: To examine whether special education racial risk ratios reported by U.S. school districts are explained by district-level confounds, particularly, racial achievement gaps, we analyzed merged data ( N = 1,952 districts for Black–White comparisons; N = 2,571 districts for Hispanic–White comparisons) from the U.S. Department of Education’s Office of Civil Rights, Stanford Educational Data Archive, and Common Core data sets. Regression analysis results indicated that Black– and Hispanic–White district risk ratios … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…Because these E- values assess for unmeasured confounding conditional on measured covariates, large unmeasured confounding resulting from factors other than those already included in recent studies would generally be necessary to explain recently reported disability under-identification of students who are Black or Hispanic. Weaker confounding than indicated by these E- values would not fully explain the recently reported disability under-identification of students who are Black or Hispanic (Farkas et al, 2020; Morgan et al, 2015, 2017). Although small-to-moderate unmeasured confounding might possibly result in null associations for some specific conditions, as mostly indicated by smaller LB 95% CIs that themselves are based on conservative E- value point estimates and conditional on each study’s measured covariates, large-to-very large unmeasured confounding would be necessary to result in levels of overidentification consistent with federal regulation.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Because these E- values assess for unmeasured confounding conditional on measured covariates, large unmeasured confounding resulting from factors other than those already included in recent studies would generally be necessary to explain recently reported disability under-identification of students who are Black or Hispanic. Weaker confounding than indicated by these E- values would not fully explain the recently reported disability under-identification of students who are Black or Hispanic (Farkas et al, 2020; Morgan et al, 2015, 2017). Although small-to-moderate unmeasured confounding might possibly result in null associations for some specific conditions, as mostly indicated by smaller LB 95% CIs that themselves are based on conservative E- value point estimates and conditional on each study’s measured covariates, large-to-very large unmeasured confounding would be necessary to result in levels of overidentification consistent with federal regulation.…”
Section: Discussionmentioning
confidence: 75%
“…Because findings of disability under-identification have been repeatedly replicated (e.g., Farkas et al, 2020; Morgan et al, 2015, 2017; Odegard et al, 2020) and, as indicated here, are largely robust to the possibility of unmeasured confounding, federal law and regulation may need to be redirected to instead monitor for systemic bias resulting in disability under-identification for students who are Black or Hispanic (Morgan et al, 2015, 2017). A recently proposed way to do so would for U.S. school districts to adjust the reported RRs for achievement gaps (Farkas et al, 2020; Morgan et al, 2017). Doing so would more accurately identify U.S. school districts where overidentification may be occurring as well as help ensure that students with disabilities who are Black or Hispanic are not being denied access to services based on their race or ethnicity.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations